Examining the ecological risk and protective factors of substance abuse and its effects on educational and behavioural outcomes among high school learners: implications for a school based intervention model - Welby-Solomon, Janine (Department of Social Development, 2021)
This study was an exploration into the Ecological Risk and Protective Factors on Adolescent Substance Use and its Effects on Behavioural and Educational Outcomes. The data was gathered using a qualitative research approach. Focus groups were conducted with the assistance of a semistructure interview guide to gather information on the research topic. The researcher used gatekeepers within Arcadia High School, Bonteheuwel High School and The College of Science and Technology school environments to gain access to participants. A non-probability sampling method was used to select 37 participants. Participants either identified as Coloured or Black, between the ages of 13 and 18 years old and were all high school students. The interviews were recorded, transcribed and Tesch was used to create a framework of analysis. The main assumptions of the study were as followed: ● Adolescent substance use is not only influenced by individual characteristics but also family, environmental and peer influences; ● Protective factors against adolescent substance use include strong familial bonds, positive peer influences and attachment to the schooling environment. ● Adolescent substance use has a negative effect on behavioural outcomes. ● Adolescent substance use has a negative effect on educational outcomes. The findings of the study show that there were a number of factors that contributed towards the vulnerability of adolescents that ultimately resulted in them using substances. Environmental factors such as poverty played a crucial role in substance use behaviours. Similarly, family influences, such as parental substance abuse and lack of parent-child connection contributed towards adolescent socialization around substance use and substance- use behaviours. The predominant protective factor appeared to be the school environment. The school environment acted as a pseudo family for adolescents where they felt safe, protected and received positive emotions such as love and understanding. The researcher recommends the development of a multi-level intervention approach that addresses the imbalances in the adolescents immediate and non-immediate environments that contribute to their substance use behaviours. This multi-level intervention strategy will run parallel to the Life Orientation programme and will focus on multiple levels of psychosocial intervention strategies that will assist adolescents in dealing with substance use.